2021
DOI: 10.1007/s11069-021-04784-9
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical surveys integrated with rainfall data analysis for the study of soil piping phenomena occurred in a densely urbanized area in eastern Sicily

Abstract: The occurrence of strong and abrupt rainfall, together with a wrong land use planning and an uncontrolled urban development, can constitute a risk for infrastructure and population. The water flow in the subsoil, under certain conditions, may cause underground cavities formation. This phenomena known as soil piping can evolve and generate the surface collapse. It is clear that such phenomena in densely urbanized areas represent an unpredictable and consistent risk factor, which can interfere with social activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…In line with previous studies (Ahmed & Carpenter, 2003; Bernatek‐Jakiel & Kondracka, 2016; Bovi et al, 2020; Cardarelli et al, 2014; Giampaolo et al, 2016; Joshi et al, 2021; Leslie & Heinse, 2013; Patti et al, 2021), soil pipes in the study area are presented as zones of higher ER on the ERT profiles (Figure 8) because the air filling the pipes behaves as an insulator (Samouëlian et al, 2005). In the study area, ER above 268 Ωm indicates the zones affected by piping erosion, whereas clear pipes are marked by ER >427 Ωm (Figure 8).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with previous studies (Ahmed & Carpenter, 2003; Bernatek‐Jakiel & Kondracka, 2016; Bovi et al, 2020; Cardarelli et al, 2014; Giampaolo et al, 2016; Joshi et al, 2021; Leslie & Heinse, 2013; Patti et al, 2021), soil pipes in the study area are presented as zones of higher ER on the ERT profiles (Figure 8) because the air filling the pipes behaves as an insulator (Samouëlian et al, 2005). In the study area, ER above 268 Ωm indicates the zones affected by piping erosion, whereas clear pipes are marked by ER >427 Ωm (Figure 8).…”
Section: Discussionsupporting
confidence: 91%
“…So far, various different geophysical methods have been explored in soil pipes detection, among which ground penetrating‐radar (GPR) (Bernatek‐Jakiel & Kondracka, 2016, 2019; Botschek et al, 2000; Got et al, 2014; Holden, 2004, 2006; Holden et al, 2002; Wodajo et al, 2021) and electrical resistivity tomography (ERT) (Ahmed & Carpenter, 2003; Bernatek‐Jakiel & Kondracka, 2016; Bovi et al, 2020; Cardarelli et al, 2014; Giampaolo et al, 2016; Joshi et al, 2021; Leslie & Heinse, 2013; Patti et al, 2021) have received the most attention. These methods were tested to detect and visualize soil pipe networks, as well as to recognize the factors controlling piping erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Urban and developed areas may be also affected by piping erosion. It may impact buildings, roads and pavements by undermining foundations and removing structural support through tunnel enlargement and tunnel roof collapse (Beckedahl & De Villiers, 2000; Khomenko, 2006; Patti et al, 2021; Sankar et al, 2016, 2020; Valenta et al, 2021; Wilson et al, 2018). So far, the occurrence of collapses, called sinkholes, have been reported mainly in karst areas, and there are vast amounts of publications referring to this problem (e.g., Sevil et al, 2017).…”
Section: Soil Pipes and Pipe Collapses As Natural Hazardsmentioning
confidence: 99%
“…It seems that in many non‐karst areas collapses due to subsurface erosion also occur. Recently, Patti et al (2021) reported PCs and identified further areas susceptible to soil piping in a densely urbanized area in eastern Sicily, whereas Sankar et al (2016, 2020) found extensive examples of infrastructure (e.g., roads, railways, buildings) weakened or even damaged by soil piping subsidence in the Kerala region (India). These phenomena are observed in different cities in Anthrosols (Figure 4).…”
Section: Soil Pipes and Pipe Collapses As Natural Hazardsmentioning
confidence: 99%
“…For monitoring and characterizing the subsurface flow with more accuracy, the electromagnetic (EM) methods have recently been applied to geophysics and spotlighted [4,5]. Through the EM survey, it is known that the change of various physical quantities such as temperature and permittivity, i.e., electric polarizability, can potentially be detected through wave inversion or the joint inversion with the seismic data (i.e., spatio-temporal data inversion problem) and by generating electrical resistivity tomography (ERT) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%